2011
DOI: 10.1088/0953-8984/23/41/416003
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of magnons in a site-diluted dimerized frustrated antiferromagnet

Abstract: We present inelastic neutron scattering and thermodynamic measurements characterizing the magnetic excitations in a disordered non-magnetic substituted spin-liquid antiferromagnet. The parent compound Ba 3 Mn 2 O 8 is a dimerized, quasi-two-dimensional geometrically frustrated quantum disordered antiferromagnet. We substitute this compound with non-magnetic vanadium for the S = 1 manganese atoms, Ba 3 (Mn 1-x V x ) 2 O 8 , and find that the singlet-triplet excitations which dominate the spectrum of the parent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
5
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…Such phases have also been seen in other materials [26][27][28][29] and in quantum Monte Carlo simulations [30][31][32][33][34].…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Such phases have also been seen in other materials [26][27][28][29] and in quantum Monte Carlo simulations [30][31][32][33][34].…”
supporting
confidence: 62%
“…Recent experiments on disordered quantum antiferromagnets have seen evidence for novel glassy phases, particularly in bromine-doped dichloro-tetrakis-thioureanickel (DTN) [25] where both Bose and Mott glass phases of bosonic quasiparticles have been observed. Such phases have also been seen in other materials [26][27][28][29] and in quantum Monte Carlo simulations [30][31][32][33][34].…”
supporting
confidence: 62%
“…N A is Avogadro's number, β = 1/k B T and α is the number of dimers per mole (where 1 mole refers to the formula unit Ba 3 (Mn 1−x V x ) 2 O 8 , such that α = 1 for x = 0). Recent INS studies found a negligible concentration dependence of both the spin gap ∆ and the triplet bandwidth for x < 0.05 22 . Therefore values of J 0 = 16.42 K, J 1 + J 4 + 2 (J 2 + J 3 ) = 5.31 K and g = 2.07 determined from the fit of the undiluted Ba 3 Mn 2 O 8 measurement (solid black circles) were held fixed for the fits of susceptibility data for the other samples.…”
Section: Resultsmentioning
confidence: 97%
“…While many studies have investigated the static and thermodynamic properties of such systems in the presence of disorder [8][9][10][11][12][13][14][15][16], the fate of quasi-particles under disorder is only rarely studied. Experimentally, however, increasingly improving resolution in spectroscopy like inelastic neutron or light scattering as well as intentional doping to control disorder in quantum materials [17][18][19][20][21][22][23], demands theoretical predictions for dynamical correlation functions of correlated quantum matter in the presence of disorder. Disordered QSL -The Hamiltonian of the disordered QSL for a fixed disorder configuration {J} is given byJ ν,n S ν,n · S ν+1,n ,(1) where the sum runs over all rungs and n = 1, 2 denotes arXiv:1806.01717v1 [cond-mat.str-el]…”
mentioning
confidence: 99%